2023
DOI: 10.3390/cells12020268
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Mesenchymal Stromal Cells from Porcine Bone Marrow, Implanted under the Kidney Capsule, form an Ectopic Focus Containing Bone, Hematopoietic Stromal Microenvironment, and Muscles

Abstract: Multipotent mesenchymal stromal cells (MSCs) are an object of intense investigation due to their therapeutic potential. MSCs have been well studied in vitro, while their fate after implantation in vivo has been poorly analyzed. We studied the properties of MSCs from the bone marrow (BM-MSC) before and after implantation under the renal capsule using a mini pig model. Autologous BM-MSCs were implanted under the kidney capsule. After 2.5 months, ectopic foci containing bones, foci of ectopic hematopoiesis, bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Using animal models to simulate the physiological development of preterm infants of different gestational ages is a feasible research way to develop a treatment for preterm birth. As one of the large animal models, pigs are especially suitable for pediatric basic research and treatment development of preterm infants, such as intestinal development and diseases, material metabolism, and immune function shaping ( 38 , 39 ). Our study uniquely focuses on late-preterm and naturally-born piglets, a less explored model in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Using animal models to simulate the physiological development of preterm infants of different gestational ages is a feasible research way to develop a treatment for preterm birth. As one of the large animal models, pigs are especially suitable for pediatric basic research and treatment development of preterm infants, such as intestinal development and diseases, material metabolism, and immune function shaping ( 38 , 39 ). Our study uniquely focuses on late-preterm and naturally-born piglets, a less explored model in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, numerous studies 7 , 8 have reported that allotransplantation of human BM-MSCs could effectively manage the disease and enhance the prognosis of refractory SLE patients. However, as research progresses, some scholars have discovered that although BM-MSCs are widely present in the hematopoietic microenvironment and play a crucial role in hemocytogenesis and immune regulation 9 , they exhibit dysfunction in SLE patients with reduced cytokine secretion and immune regulatory abilities, decreased proliferation and differentiation capacities, abnormal cell structure, and significantly increased intracellular oxidative stress 10 . Animal experimental studies 11 also revealed that autologous BM-MSCs from SLE mice failed to migrate to target organs after transplantation in vivo , while MSCs transplanted between allogeneic groups still exhibited donor degeneration, genetic instability, and immune rejection.…”
Section: Mesenchymal Stem Cell Transplantationmentioning
confidence: 99%